2020
DOI: 10.5194/amt-2020-458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of dark current signal measurements of the ACCDs used on-board the Aeolus satellite

Abstract: Abstract. Already shortly after the successful launch of the European Space Agency satellite Aeolus in August 2018, it turned out that dark current signal anomalies of single pixels (so-called hot pixels) on the Accumulation-Charge-Coupled Devices (ACCDs) of the Aeolus detectors detrimentally impact the quality of the aerosol and wind products potentially leading to wind errors of up to 4 m/s. This paper provides a detailed characterization of the hot pixels which occurred during the first one and a half years… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Thus, on average over the validation period about 70 % of the Rayleigh and 76 % of the Mie winds are available for the analysis. On 14 June 2019 a correction scheme for dark current signal anomalies of single pixels (hot pixels) on the accumulation-charge-coupled devices (ACCDs) of the Aeolus detectors has been implemented into the Aeolus operational processor chain (Weiler et al, 2020). All measurements before 14 June 2019 affected by hot pixels are excluded from the validation statistic.…”
Section: Aeolus L2b Wind Productmentioning
confidence: 99%
“…Thus, on average over the validation period about 70 % of the Rayleigh and 76 % of the Mie winds are available for the analysis. On 14 June 2019 a correction scheme for dark current signal anomalies of single pixels (hot pixels) on the accumulation-charge-coupled devices (ACCDs) of the Aeolus detectors has been implemented into the Aeolus operational processor chain (Weiler et al, 2020). All measurements before 14 June 2019 affected by hot pixels are excluded from the validation statistic.…”
Section: Aeolus L2b Wind Productmentioning
confidence: 99%
“…Registration (Reitebuch et al, 2018), Down Under Dark Experiment (Weiler et al, 2020) or orbit correction maneuvers. The figure also illustrates the percentage of observations that are affected by enhanced frequency fluctuations.…”
Section: Frequency Stability Of the Aladin Laser Transmittersmentioning
confidence: 99%
“…This was made possible by the identification of and correction for large systematic errors which had strongly degraded the wind data quality in the initial phase of the mission (Kanitz et al, 2020;. Firstly, dark current signal anomalies on single ("hot") pixels of the Aeolus detectors which had led to wind errors of up to 4 m•s -1 were recognized and successfully accounted for by the implementation of dedicated calibration instrument modes (Weiler et al, 2020). Secondly, biases that were found to be closely correlated with small variations in the temperature distribution across the primary telescope mirror (Rennie and Isaksen, 2020a) could be corrected.…”
Section: Introductionmentioning
confidence: 99%
“…This is an official reprocessing from PDGS and contains a number of improvements of several deficiencies closely examined by ESA and DISC. This is an improved treatment for removing spurious outliers induced by dark current signals (hot pixels) (Weiler et al, 2020).…”
Section: Datasets and Level-2b Processingmentioning
confidence: 99%
“…Such is a systematic error arising due to a so-called dark current signal anomalies of single Accumulation Charge-Coupled Device (ACCD) pixels (i.e. "hot pixel") (Weiler et al, 2020) or a significant source of wind systematic error which has been found to be correlated with the temperature gradients across the Atmospheric averaged), the main goal of this paper is to explore the impact of uncertainty in modelled temperature and pressure fields for the retrieval of Rayleigh HLOS winds.…”
Section: Introductionmentioning
confidence: 99%